A temperature-control resin material, preparation method and application thereof on shoe soles
By combining TPU resin and polylactic acid in temperature-controlled resin materials, and using regulators based on carbon nanotube modification and sheet-shaped talc powder assembly agent, the problem of unbalanced performance of existing materials is solved, significantly improving the antibacterial durability , tensile strength and resilience, and enhance aging resistance and cold resistance.
Patent Information
- Application Number
- CN202411449057.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The existing temperature-controlled resin materials have poor performance in antibacterial durability, tensile strength and resilience, which is difficult to achieve balance, and are not able to resist aging and cold resistance, which limits the efficiency of the product.
Using TPU resin combined with polylactic acid, antibacterial agent, foaming agent, stearic acid, antioxidant and modifier based on carbon nanotube modification, optimize the carbon nanotube and sheet talc powder through specific preparation methods. Performance, coordinate and coordinate to improve the performance of the material.
The coordinated balance of antibacterial durability and tensile strength is achieved, which significantly improves the material's aging resistance and cold resistance stability. The temperature can be controlled between 24℃~28℃, and the product performance is significantly improved.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of temperature control resin materials, and in particular to a temperature control resin material, a preparation method and application thereof on shoe soles. Background Art
[0002] Shoes are used to protect the feet and facilitate walking, usually made of leather, cloth, rubber and other materials. With the development of science and technology and the improvement of people's living standards, people's demand for the performance of shoes is also increasing.
[0003] Although the resin materials used in existing shoes can achieve temperature control performance by using temperature control materials, the resin materials have poor antibacterial durability, poor tensile strength and resilience, and it is difficult for the product to achieve a balance in performance. In addition, the product has poor aging resistance and cold resistance, which further limits the product's efficiency. Summary of the invention
[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a temperature-controlled resin material, a preparation method and application thereof on the soles, so as to solve the problems raised in the above-mentioned background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution:
[0006] The present invention provides a temperature-control resin material, comprising the following raw materials in parts by weight:
[0007] 25-35 parts of TPU resin, 35-40 parts of polylactic acid, 7-11 parts of carbon nanotube-modified regulator, 5-8 parts of antibacterial agent, 4-7 parts of flaky talc assembly agent, 3-5 parts of foaming agent, 2-3 parts of stearic acid, 2-4 parts of antioxidant, and 2-4 parts of silane coupling agent KH560.
[0008] Preferably, the foaming agent is azodicarbonamide; the antioxidant is antioxidant 1010; and the antibacterial agent is a mixture of nano silver powder and nano zinc oxide powder in a weight ratio of 3:2.
[0009] Preferably, the preparation method of the carbon nanotube-modified regulator is:
[0010] S01: Preparation of modified carbon nanotube agent:
[0011] S011: irradiating the carbon nanotubes in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W, and obtaining an irradiated carbon nanotube agent after the irradiation is completed;
[0012] S012: Add 2-4 parts of citric acid and 1-3 parts of sodium dodecylbenzene sulfonate to 4-7 parts of 3-5% by mass sodium silicate solution, and then add 2-3 parts of silane coupling agent KH550 and mix thoroughly to obtain a modified solution;
[0013] S013: stirring the irradiated carbon nanotube agent and the modifying liquid at a weight ratio of 2:5 for modification treatment, washing with water and drying after the stirring is completed to obtain a modified carbon nanotube agent;
[0014] S02: adding 4-7 parts of hydroxyapatite and 2-3 parts of nano-silica sol to 5-8 parts of lanthanum chloride solution, and then adding 2-3 parts of chitosan solution and mixing thoroughly to obtain an effect-adjusting solution;
[0015] S03: The modified carbon nanotube agent and the conditioning liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1500 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain a conditioning agent modified based on carbon nanotubes.
[0016] Preferably, the mass fraction of the lanthanum chloride solution is 4-7%; the mass fraction of the chitosan solution is 2-5%.
[0017] Preferably, the stirring speed of the stirring modification treatment is 450-550 r / min, and the stirring time is 30-40 min.
[0018] Preferably, the preparation method of the flaky talc assembly is:
[0019] S11: heating the flaky talc powder to 125-130° C. at a rate of 1-3° C. / min, keeping the temperature for 5-10 min, and then air-cooling the flaky talc powder to 55° C. and keeping the temperature to obtain a heat-insulated flaky talc powder;
[0020] S12: fully mixing 2-4 parts by mass of 5% yttrium nitrate solution, 1-3 parts by mass of phosphate buffer solution and 4-7 parts by mass of 2-5% sodium alginate solution to obtain yttrium solution;
[0021] The insulated flaky talc powder and yttrium liquid were mixed in a weight ratio of 4:3 and ball-milled at a speed of 1000-1500 r / min for 2 h to obtain yttrium-adjusted flaky talc;
[0022] S13: The yttrium-adjusted flaky talc and the self-adjusting agent are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1000 r / min for 1 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a flaky talc powder assembly agent.
[0023] Preferably, the pH value of the phosphate buffer solution is 5.0-5.5.
[0024] Preferably, the preparation method of the self-adjusting agent is:
[0025] Preheat the nano-bentonite at 135-145°C for 5-10 minutes, then heat it to 235-245°C at a rate of 1-3°C / min, keep it warm for 5 minutes, and finally air-cool it to room temperature;
[0026] 5-8 parts of the above nano-bentonite cooled to room temperature by air, 2-5 parts of nano-silicon dioxide and 4-7 parts of sodium lignin sulfonate solution are fully blended to obtain a self-adjusting agent.
[0027] Preferably, the mass fraction of the sodium lignin sulfonate solution is 4-7%.
[0028] The present invention also provides a method for preparing a temperature-controlled resin material, comprising the following steps:
[0029] First, TPU resin and polylactic acid are fed into an open mill, with a roller spacing of 5mm and thin pass twice to obtain a premix; then the premix is rolled, and then a carbon nanotube-modified regulator, an antibacterial agent, a flaky talcum powder assembly agent, a foaming agent, stearic acid, an antioxidant and a silane coupling agent KH560 are added, with a roller spacing of 5mm and thin pass three times, a roller spacing of 2mm and thin pass five times, triangle wrapping three times, and sheeting to obtain a sheet; finally, the sheet is put into a mold for molding, the mold temperature is 195°C, the pressure is 8MPa, the molding is 5min, and the mold is cooled and demolded to obtain a temperature-controlled resin material.
[0030] The invention also provides an application of the temperature-control resin material on the sole.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The temperature control resin material of the present invention adopts TPU resin and polylactic acid, and adds antibacterial agent, foaming agent, stearic acid, antioxidant, silane coupling agent KH560 as functional additives, and adds a regulator based on carbon nanotube modification and a flaky talcum powder assembly agent. The two are coordinated and matched, and the product has excellent antibacterial durability, tensile strength and resilience. The product can achieve a coordinated balance of performance, and the product has significant effects on aging resistance and cold resistance stability.
[0033] The regulator based on carbon nanotube modification uses flaky talcum powder to first heat up to 125-130℃ at a rate of 1-3℃ / min, keep warm for 5-10min, and then air cool to 55℃. Through thermal improvement treatment, its active performance is optimized. Citric acid, sodium dodecylbenzene sulfonate, 3-5% sodium silicate solution by mass and silane coupling agent KH550 are blended and coordinated. Then, through the coordination and mutual assistance between the modified liquids, the activity and interface performance of the carbon nanotubes are enhanced. At the same time, hydroxyapatite is used as a point-coordinating agent and attached to the carbon nanotube matrix to optimize the performance of the carbon nanotubes. At the same time, the high specific surface area structure of the carbon nanotubes is used to achieve a temperature control effect, and the temperature can be controlled at 24℃~28℃. At the same time, the hydroxyapatite, nano-silica sol, lanthanum chloride solution and chitosan solution in the effect-adjusting liquid are blended and assisted to enhance each other, and the coordinated performance of the product's antibacterial durability, tensile strength and resilience is further improved and enhanced.
[0034] The flaky talc powder assembly agent is first heated to 125-130°C at a rate of 1-3°C / min, kept warm for 5-10 minutes, and then air-cooled to 55°C to optimize its active efficacy, and then fully blended with yttrium nitrate solution, phosphate buffer solution and 2-5% by mass sodium alginate solution to obtain yttrium liquid, and the yttrium liquid is prepared by the flaky talc powder of S11 for improvement, so as to facilitate better coordination of talc with self-adjusting agent, the self-adjusting agent is improved by staged thermal improvement of lamellar nano-bentonite to optimize its lamellar structure, and at the same time, the self-adjusting agent is fully blended with nano-silicon dioxide and sodium lignin sulfonate solution to obtain the self-adjusting agent, and the bentonite raw material is assisted by nano-silicon dioxide, and the flaky talc powder is assembled by bentonite, so as to be interspersed and matched into the system, so as to further improve the coordinated balance of product performance, and enhance the product's aging resistance and cold stability. DETAILED DESCRIPTION
[0035] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] A temperature-control resin material of this embodiment includes the following raw materials in parts by weight:
[0037] 25-35 parts of TPU resin, 35-40 parts of polylactic acid, 7-11 parts of carbon nanotube-modified regulator, 5-8 parts of antibacterial agent, 4-7 parts of flaky talc assembly agent, 3-5 parts of foaming agent, 2-3 parts of stearic acid, 2-4 parts of antioxidant, and 2-4 parts of silane coupling agent KH560.
[0038] The foaming agent of this embodiment is azodicarbonamide; the antioxidant is antioxidant 1010; and the antibacterial agent is a mixture of nano silver powder and nano zinc oxide powder in a weight ratio of 3:2.
[0039] The preparation method of the regulator based on carbon nanotube modification in this embodiment is:
[0040] S01: Preparation of modified carbon nanotube agent:
[0041] S011: irradiating the carbon nanotubes in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W, and obtaining an irradiated carbon nanotube agent after the irradiation is completed;
[0042] S012: Add 2-4 parts of citric acid and 1-3 parts of sodium dodecylbenzene sulfonate to 4-7 parts of 3-5% by mass sodium silicate solution, and then add 2-3 parts of silane coupling agent KH550 and mix thoroughly to obtain a modified solution;
[0043] S013: stirring the irradiated carbon nanotube agent and the modifying liquid at a weight ratio of 2:5 for modification treatment, washing with water and drying after the stirring is completed to obtain a modified carbon nanotube agent;
[0044] S02: adding 4-7 parts of hydroxyapatite and 2-3 parts of nano-silica sol to 5-8 parts of lanthanum chloride solution, and then adding 2-3 parts of chitosan solution and mixing thoroughly to obtain an effect-adjusting solution;
[0045] S03: The modified carbon nanotube agent and the conditioning liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1500 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain a conditioning agent modified based on carbon nanotubes.
[0046] The mass fraction of the lanthanum chloride solution in this embodiment is 4-7%; the mass fraction of the chitosan solution is 2-5%.
[0047] The stirring speed of the stirring modification treatment in this embodiment is 450-550 r / min, and the stirring time is 30-40 min.
[0048] The preparation method of the flaky talc powder assembly of this embodiment is as follows:
[0049] S11: heating the flaky talc powder to 125-130° C. at a rate of 1-3° C. / min, keeping the temperature for 5-10 min, and then air-cooling the flaky talc powder to 55° C. and keeping the temperature to obtain a heat-insulated flaky talc powder;
[0050] S12: fully mixing 2-4 parts by mass of 5% yttrium nitrate solution, 1-3 parts by mass of phosphate buffer solution and 4-7 parts by mass of 2-5% sodium alginate solution to obtain yttrium solution;
[0051] The insulated flaky talc powder and yttrium liquid were mixed in a weight ratio of 4:3 and ball-milled at a speed of 1000-1500 r / min for 2 h to obtain yttrium-adjusted flaky talc;
[0052] S13: The yttrium-adjusted flaky talc and the self-adjusting agent are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1000 r / min for 1 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a flaky talc powder assembly agent.
[0053] The pH value of the phosphate buffer solution of this embodiment is 5.0-5.5.
[0054] The preparation method of the self-adjusting agent of the present embodiment is:
[0055] Preheat the nano-bentonite at 135-145°C for 5-10 minutes, then heat it to 235-245°C at a rate of 1-3°C / min, keep it warm for 5 minutes, and finally air-cool it to room temperature;
[0056] 5-8 parts of the above nano-bentonite cooled to room temperature by air, 2-5 parts of nano-silicon dioxide and 4-7 parts of sodium lignin sulfonate solution are fully blended to obtain a self-adjusting agent.
[0057] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 4-7%.
[0058] A method for preparing a temperature-controlled resin material according to this embodiment includes the following steps:
[0059] First, TPU resin and polylactic acid are fed into an open mill, with a roller spacing of 5mm and thin pass twice to obtain a premix; then the premix is rolled, and then a carbon nanotube-modified regulator, an antibacterial agent, a flaky talcum powder assembly agent, a foaming agent, stearic acid, an antioxidant and a silane coupling agent KH560 are added, with a roller spacing of 5mm and thin pass three times, a roller spacing of 2mm and thin pass five times, triangle wrapping three times, and sheeting to obtain a sheet; finally, the sheet is put into a mold for molding, the mold temperature is 195°C, the pressure is 8MPa, the molding is 5min, and the mold is cooled and demolded to obtain a temperature-controlled resin material.
[0060] Embodiment 1: A temperature-control resin material, comprising the following raw materials in parts by weight:
[0061] 25 parts of TPU resin, 35 parts of polylactic acid, 7 parts of carbon nanotube-modified regulator, 5 parts of antibacterial agent, 4 parts of flaky talc assembly agent, 3 parts of foaming agent, 2 parts of stearic acid, 2 parts of antioxidant, and 2 parts of silane coupling agent KH560.
[0062] The foaming agent of this embodiment is azodicarbonamide; the antioxidant is antioxidant 1010; and the antibacterial agent is a mixture of nano silver powder and nano zinc oxide powder in a weight ratio of 3:2.
[0063] The preparation method of the regulator based on carbon nanotube modification in this embodiment is:
[0064] S01: Preparation of modified carbon nanotube agent:
[0065] S011: irradiating the carbon nanotubes in a proton irradiation box for 5 minutes at an irradiation power of 350 W, and obtaining an irradiated carbon nanotube agent after the irradiation is completed;
[0066] S012: Add 2 parts of citric acid and 1 part of sodium dodecylbenzene sulfonate to 4 parts of 3% sodium silicate solution, and then add 2 parts of silane coupling agent KH550 and mix thoroughly to obtain a modified solution;
[0067] S013: stirring the irradiated carbon nanotube agent and the modifying liquid at a weight ratio of 2:5 for modification treatment, washing with water and drying after the stirring is completed to obtain a modified carbon nanotube agent;
[0068] S02: Add 4 parts of hydroxyapatite and 2 parts of nano-silica sol to 5 parts of lanthanum chloride solution, and then add 2 parts of chitosan solution and mix thoroughly to obtain an effect-adjusting solution;
[0069] S03: The modified carbon nanotube agent and the conditioning liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1500 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain a conditioning agent modified based on carbon nanotubes.
[0070] The mass fraction of the lanthanum chloride solution in this embodiment is 4%; the mass fraction of the chitosan solution is 2%.
[0071] The stirring speed of the stirring modification treatment in this embodiment is 450 r / min, and the stirring time is 30 min.
[0072] The preparation method of the flaky talc powder assembly of this embodiment is as follows:
[0073] S11: heating the flaky talc powder to 125° C. at a rate of 1° C. / min, keeping the temperature for 5 minutes, and then air-cooling the flaky talc powder to 55° C. and keeping the temperature to obtain a heat-insulated flaky talc powder;
[0074] S12: fully mixing 2 parts of 5% by mass yttrium nitrate solution, 1 part of phosphate buffer solution and 4 parts of 2% by mass sodium alginate solution to obtain yttrium solution;
[0075] The insulated flaky talc powder and yttrium solution were mixed in a weight ratio of 4:3 and ball-milled at a ball-milling speed of 1000 r / min for 2 h to obtain yttrium-adjusted flaky talc;
[0076] S13: The yttrium-adjusted flaky talc and the self-adjusting agent are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1000 r / min for 1 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a flaky talc powder assembly agent.
[0077] The pH value of the phosphate buffer solution in this example is 5.0.
[0078] The preparation method of the self-adjusting agent of the present embodiment is:
[0079] The nano-bentonite was preheated at 135°C for 5 min, then heated to 235°C at a rate of 1°C / min, kept warm for 5 min, and finally air-cooled to room temperature.
[0080] 5 parts of the above nano-bentonite cooled to room temperature by air, 2 parts of nano-silicon dioxide and 4 parts of sodium lignin sulfonate solution are fully blended to obtain a self-adjusting agent.
[0081] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 4%.
[0082] A method for preparing a temperature-controlled resin material according to this embodiment includes the following steps:
[0083] First, TPU resin and polylactic acid are fed into an open mill, with a roller spacing of 5mm and thin pass twice to obtain a premix; then the premix is rolled, and then a carbon nanotube-modified regulator, an antibacterial agent, a flaky talcum powder assembly agent, a foaming agent, stearic acid, an antioxidant and a silane coupling agent KH560 are added, with a roller spacing of 5mm and thin pass three times, a roller spacing of 2mm and thin pass five times, triangle wrapping three times, and sheeting to obtain a sheet; finally, the sheet is put into a mold for molding, the mold temperature is 195°C, the pressure is 8MPa, the molding is 5min, and the mold is cooled and demolded to obtain a temperature-controlled resin material.
[0084] Embodiment 2: A temperature-control resin material, comprising the following raw materials in parts by weight:
[0085] 35 parts of TPU resin, 40 parts of polylactic acid, 11 parts of carbon nanotube-modified regulator, 8 parts of antibacterial agent, 7 parts of flaky talc assembly agent, 5 parts of foaming agent, 3 parts of stearic acid, 4 parts of antioxidant, and 4 parts of silane coupling agent KH560.
[0086] The foaming agent of this embodiment is azodicarbonamide; the antioxidant is antioxidant 1010; and the antibacterial agent is a mixture of nano silver powder and nano zinc oxide powder in a weight ratio of 3:2.
[0087] The preparation method of the regulator based on carbon nanotube modification in this embodiment is:
[0088] S01: Preparation of modified carbon nanotube agent:
[0089] S011: irradiating the carbon nanotubes in a proton irradiation box for 10 minutes at an irradiation power of 400 W, and obtaining an irradiated carbon nanotube agent after the irradiation is completed;
[0090] S012: 4 parts of citric acid and 3 parts of sodium dodecylbenzene sulfonate are added to 7 parts of 5% sodium silicate solution by mass, and then 3 parts of silane coupling agent KH550 are added and mixed thoroughly to obtain a modified solution;
[0091] S013: stirring the irradiated carbon nanotube agent and the modifying liquid at a weight ratio of 2:5 for modification treatment, washing with water and drying after the stirring is completed to obtain a modified carbon nanotube agent;
[0092] S02: adding 7 parts of hydroxyapatite and 3 parts of nano-silica sol to 8 parts of lanthanum chloride solution, and then adding 3 parts of chitosan solution and mixing thoroughly to obtain an effect-adjusting solution;
[0093] S03: The modified carbon nanotube agent and the conditioning liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1500 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain a conditioning agent modified based on carbon nanotubes.
[0094] The mass fraction of the lanthanum chloride solution in this embodiment is 7%; the mass fraction of the chitosan solution is 5%.
[0095] The stirring speed of the stirring modification treatment in this embodiment is 550 r / min, and the stirring time is 40 min.
[0096] The preparation method of the flaky talc powder assembly of this embodiment is as follows:
[0097] S11: heating the flaky talc powder to 130° C. at a rate of 3° C. / min, keeping the temperature for 10 min, and then air-cooling the flaky talc powder to 55° C. and keeping the temperature to obtain a heat-insulated flaky talc powder;
[0098] S12: fully mixing 4 parts of 5% by mass yttrium nitrate solution, 3 parts of phosphate buffer solution and 7 parts of 5% by mass sodium alginate solution to obtain yttrium solution;
[0099] The insulated flaky talc powder and yttrium solution were mixed in a weight ratio of 4:3 and ball-milled at a speed of 1500 r / min for 2 h to obtain yttrium-adjusted flaky talc;
[0100] S13: The yttrium-adjusted flaky talc and the self-adjusting agent are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1000 r / min for 1 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a flaky talc powder assembly agent.
[0101] The pH value of the phosphate buffer solution in this example is 5.5.
[0102] The preparation method of the self-adjusting agent of the present embodiment is:
[0103] The nano-bentonite was preheated at 145°C for 10 min, then heated to 245°C at a rate of 3°C / min, kept warm for 5 min, and finally air-cooled to room temperature.
[0104] 8 parts of the above nano-bentonite cooled to room temperature, 5 parts of nano-silicon dioxide and 7 parts of sodium lignin sulfonate solution were fully blended to obtain a self-adjusting agent.
[0105] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 7%.
[0106] A method for preparing a temperature-controlled resin material according to this embodiment includes the following steps:
[0107] First, TPU resin and polylactic acid are fed into an open mill, with a roller spacing of 5mm and thin pass twice to obtain a premix; then the premix is rolled, and then a carbon nanotube-modified regulator, an antibacterial agent, a flaky talcum powder assembly agent, a foaming agent, stearic acid, an antioxidant and a silane coupling agent KH560 are added, with a roller spacing of 5mm and thin pass three times, a roller spacing of 2mm and thin pass five times, triangle wrapping three times, and sheeting to obtain a sheet; finally, the sheet is put into a mold for molding, the mold temperature is 195°C, the pressure is 8MPa, the molding is 5min, and the mold is cooled and demolded to obtain a temperature-controlled resin material.
[0108] Embodiment 3: A temperature-control resin material, comprising the following raw materials in parts by weight:
[0109] 30 parts of TPU resin, 37.5 parts of polylactic acid, 8.5 parts of carbon nanotube-modified regulator, 6.5 parts of antibacterial agent, 5.5 parts of flaky talc assembly agent, 4 parts of foaming agent, 2.5 parts of stearic acid, 3 parts of antioxidant, and 3 parts of silane coupling agent KH560.
[0110] The foaming agent of this embodiment is azodicarbonamide; the antioxidant is antioxidant 1010; and the antibacterial agent is a mixture of nano silver powder and nano zinc oxide powder in a weight ratio of 3:2.
[0111] The preparation method of the regulator based on carbon nanotube modification in this embodiment is:
[0112] S01: Preparation of modified carbon nanotube agent:
[0113] S011: irradiating the carbon nanotubes in a proton irradiation box for 7.5 minutes at an irradiation power of 370 W, and obtaining an irradiated carbon nanotube agent after the irradiation is completed;
[0114] S012: Add 3 parts of citric acid and 2 parts of sodium dodecylbenzene sulfonate to 5.5 parts of 4% sodium silicate solution, and then add 2.5 parts of silane coupling agent KH550 and mix thoroughly to obtain a modified solution;
[0115] S013: stirring the irradiated carbon nanotube agent and the modifying liquid at a weight ratio of 2:5 for modification treatment, washing with water and drying after the stirring is completed to obtain a modified carbon nanotube agent;
[0116] S02: Add 5.5 parts of hydroxyapatite and 2.5 parts of nano-silica sol to 6.5 parts of lanthanum chloride solution, and then add 2.5 parts of chitosan solution and mix thoroughly to obtain an effect-adjusting solution;
[0117] S03: The modified carbon nanotube agent and the conditioning liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1500 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain a conditioning agent modified based on carbon nanotubes.
[0118] The mass fraction of the lanthanum chloride solution in this embodiment is 5.5%; the mass fraction of the chitosan solution is 3.5%.
[0119] The stirring speed of the stirring modification treatment in this embodiment is 500 r / min, and the stirring time is 35 min.
[0120] The preparation method of the flaky talc powder assembly of this embodiment is as follows:
[0121] S11: heating the flaky talc powder to 127° C. at a rate of 2° C. / min, keeping the temperature for 7.5 min, and then air-cooling the flaky talc powder to 55° C. and keeping the temperature to obtain a heat-insulated flaky talc powder;
[0122] S12: fully mixing 3 parts of 5% by mass yttrium nitrate solution, 2 parts of phosphate buffer solution and 5.5 parts of 3.5% by mass sodium alginate solution to obtain yttrium solution;
[0123] The insulated flaky talc powder and yttrium solution were mixed and ball-milled at a weight ratio of 4:3 at a ball-milling speed of 1250 r / min for 2 h to obtain yttrium-adjusted flaky talc;
[0124] S13: The yttrium-adjusted flaky talc and the self-adjusting agent are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1000 r / min for 1 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a flaky talc powder assembly agent.
[0125] The pH value of the phosphate buffer solution in this example is 5.2.
[0126] The preparation method of the self-adjusting agent of the present embodiment is:
[0127] The nano-bentonite was preheated at 140°C for 7.5 min, then heated to 240°C at a rate of 2°C / min, kept warm for 5 min, and finally air-cooled to room temperature.
[0128] 6.5 parts of the above nano-bentonite cooled to room temperature in air, 3.5 parts of nano-silicon dioxide and 5.5 parts of sodium lignin sulfonate solution were fully blended to obtain a self-adjusting agent.
[0129] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 5.5%.
[0130] A method for preparing a temperature-controlled resin material according to this embodiment includes the following steps:
[0131] First, TPU resin and polylactic acid are fed into an open mill, with a roller spacing of 5mm and thin pass twice to obtain a premix; then the premix is rolled, and then a carbon nanotube-modified regulator, an antibacterial agent, a flaky talcum powder assembly agent, a foaming agent, stearic acid, an antioxidant and a silane coupling agent KH560 are added, with a roller spacing of 5mm and thin pass three times, a roller spacing of 2mm and thin pass five times, triangle wrapping three times, and sheeting to obtain a sheet; finally, the sheet is put into a mold for molding, the mold temperature is 195°C, the pressure is 8MPa, the molding is 5min, and the mold is cooled and demolded to obtain a temperature-controlled resin material.
[0132] Comparative Example 1:
[0133] The difference from Example 3 is that no regulator based on carbon nanotube modification is added.
[0134] Comparative Example 2:
[0135] The difference from Example 3 is that no modification liquid is added during the preparation of the regulator based on carbon nanotube modification.
[0136] Comparative Example 3:
[0137] The difference from Example 3 is that no conditioning liquid is added during the preparation of the conditioning agent modified based on carbon nanotubes.
[0138] Comparative Example 4:
[0139] The difference from Example 3 is that no hydroxyapatite or nano-silica sol is added to the conditioning solution.
[0140] Comparative Example 5:
[0141] The difference from Example 3 is that no chitosan solution is added to the conditioning solution and the lanthanum chloride solution is replaced by deionized water.
[0142] Comparative Example 6:
[0143] The difference from Example 3 is that no flaky talc assembling agent is added.
[0144] Comparative Example 7:
[0145] The difference from Example 3 is that no yttrium-adjusted flaky talc is added to the flaky talc powder assembly.
[0146] Comparative Example 8:
[0147] The difference from Example 3 is that flaky talc powder is directly used in the preparation of the yttrium-adjusted flaky talc.
[0148] Comparative Example 9:
[0149] The difference from Example 3 is that no self-adjusting treatment is used in the flaky talc assembly.
[0150] Comparative Example 10:
[0151] The difference from Example 3 is that the nano-bentonite cooled to room temperature by air is not added to the self-adjusting agent.
[0152] Comparative Example 11:
[0153] The difference from Example 3 is that no nano silicon dioxide and sodium lignin sulfonate solution are added to the self-adjusting agent.
[0154] The performance of the products of Examples 1-3 and Comparative Examples 1-11 was tested under normal conditions, and the performance test results are shown in Table 1.
[0155] Table 1: Performance test results of the products of Examples 1-3 and Comparative Examples 1-11 under normal conditions It can be concluded from Table 1 that the products of Examples 1-3 have excellent 48h Escherichia coli antibacterial rate, rebound rate and tensile strength performance, and the antibacterial, rebound rate and tensile strength performance of the products can be coordinated and improved. The product performances of Examples 1-3 are significantly better than those of Comparative Examples 1-11.
[0156] The test product was placed at -5°C for 6 hours, then at 65°C and 500 pphm ozone for 2 hours, and then at 340nm and 0.5W / m 2 The product was placed under a xenon lamp with a wavelength of .nm for 2 hours. The above is one cycle. The product was cycled 10 times to test its aging resistance and cold resistance stability. The test results are shown in Table 2.
[0157] Table 2: Test results of aging resistance and cold resistance stability of products of Examples 1-3 and Comparative Examples 1-11 It can be concluded from Table 2 that the product of Example 3 of the present invention has significant effects on the stability of the 48h Escherichia coli antibacterial rate, rebound rate and tensile strength performance of the product in an aging-resistant and cold-resistant environment;
[0158] From Comparative Examples 1-11 and Example 3, it can be seen that the performance of the products without adding a carbon nanotube-modified regulator or a flaky talc assembly agent has a significant deterioration trend. The performance effect of the products is most significant when the two are coordinated and work together.
[0159] The performance of the products tended to deteriorate when no modifying liquid was added in the preparation of the carbon nanotube-modified conditioning agent, no conditioning liquid was added in the preparation of the carbon nanotube-modified conditioning agent, no hydroxyapatite and nano-silica sol were added to the conditioning liquid, no chitosan solution was added to the conditioning liquid, and the lanthanum chloride solution was replaced by deionized water. Only when the modified liquid obtained by the method of the present invention was combined with the conditioning liquid of the present invention, the performance effect of the product was the most obvious.
[0160] The performance of the products of the flaky talc powder assemblies without adding yttrium-adjusted flaky talc, directly replacing the yttrium-adjusted flaky talc in the preparation of the flaky talc, not using self-adjusting agent treatment in the flaky talc powder assemblies, not adding nano-bentonite air-cooled to room temperature in the self-adjusting agent, and not adding nano-silicon dioxide and sodium lignin sulfonate solution in the self-adjusting agent all tend to deteriorate. The performance of the flaky talc powder assemblies obtained by different methods all tend to deteriorate to varying degrees. The performance effect of the product is most significant when the specific self-adjusting agent of the present invention is combined with the yttrium-adjusted flaky talc of the present invention, and the effect of other replacement methods is not as obvious as that of the present invention.
[0161] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0162] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A temperature control resin material, characterized in that: It includes the following raw materials in parts by weight: 25-35 parts of TPU resin, 35-40 parts of polylactic acid, 7-11 parts of carbon nanotube-modified regulator, 5-8 parts of antibacterial agent, 4-7 parts of flaky talc assembly agent, 3-5 parts of foaming agent, 2-3 parts of stearic acid, 2-4 parts of antioxidant, 2-4 parts of silane coupling agent KH560; The preparation method of the carbon nanotube-modified regulator is as follows: S01: Preparation of modified carbon nanotube agent: S011: irradiating the carbon nanotubes in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W, and obtaining an irradiated carbon nanotube agent after the irradiation is completed; S012: Add 2-4 parts of citric acid and 1-3 parts of sodium dodecylbenzene sulfonate to 4-7 parts of 3-5% by mass sodium silicate solution, and then add 2-3 parts of silane coupling agent KH550 and mix thoroughly to obtain a modified solution; S013: stirring the irradiated carbon nanotube agent and the modifying liquid at a weight ratio of 2:5 for modification treatment, washing with water and drying after the stirring is completed to obtain a modified carbon nanotube agent; S02: adding 4-7 parts of hydroxyapatite and 2-3 parts of nano-silica sol to 5-8 parts of lanthanum chloride solution, and then adding 2-3 parts of chitosan solution and mixing thoroughly to obtain an effect-adjusting solution; S03: The modified carbon nanotube agent and the conditioning liquid are mixed in a weight ratio of 5:3 and subjected to ball milling treatment at a ball milling speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is washed with water and dried to obtain a conditioning agent modified with carbon nanotubes; The preparation method of the flaky talc powder assembly agent is as follows: S11: heating the flaky talc powder to 125-130° C. at a rate of 1-3° C. / min, keeping the temperature for 5-10 min, and then air-cooling the flaky talc powder to 55° C. and keeping the temperature to obtain a heat-insulated flaky talc powder; S12: fully mixing 2-4 parts by mass of 5% yttrium nitrate solution, 1-3 parts by mass of phosphate buffer solution and 4-7 parts by mass of 2-5% sodium alginate solution to obtain yttrium solution; The insulated flaky talc powder and yttrium liquid were mixed in a weight ratio of 4:3 and ball-milled at a speed of 1000-1500 r / min for 2 h to obtain yttrium-adjusted flaky talc; S13: mixing the yttrium-adjusted flaky talc and the self-adjusting agent in a weight ratio of 5:3, and ball milling the mixture at a speed of 1000 r / min for 1 h. After the ball milling is completed, washing and drying are performed to obtain a flaky talc powder assembly agent; The preparation method of the self-adjusting agent is: Preheat the nano-bentonite at 135-145°C for 5-10 minutes, then heat it to 235-245°C at a rate of 1-3°C / min, keep it warm for 5 minutes, and finally air-cool it to room temperature; 5-8 parts of the above-mentioned nano-bentonite cooled to room temperature by air, 2-5 parts of nano-silicon dioxide and 4-7 parts of sodium lignin sulfonate solution are fully blended to obtain a self-adjusting agent; the mass fraction of the sodium lignin sulfonate solution is 4-7%.
2. A temperature control resin material according to claim 1, characterized in that: The foaming agent is azodicarbonamide; the antioxidant is antioxidant 1010; and the antibacterial agent is a mixture of nano silver powder and nano zinc oxide powder in a weight ratio of 3:
2.
3. A temperature control resin material according to claim 1, characterized in that: The mass fraction of the lanthanum chloride solution is 4-7%; the mass fraction of the chitosan solution is 2-5%.
4. A temperature-control resin material according to claim 1, characterized in that: The stirring speed of the stirring modification treatment is 450-550 r / min, and the stirring time is 30-40 min.
5. The temperature control resin material according to claim 1, characterized in that: The pH value of the phosphate buffer solution is 5.0-5.
5.
6. A method for preparing a temperature-controlling resin material, for preparing the temperature-controlling resin material according to any one of claims 1 to 5, characterized in that: The following steps are involved: First, TPU resin and polylactic acid are fed into an open mill, with a roller spacing of 5mm and thin pass twice to obtain a premix; then the premix is rolled, and then a carbon nanotube-modified regulator, an antibacterial agent, a flaky talcum powder assembly agent, a foaming agent, stearic acid, an antioxidant and a silane coupling agent KH560 are added, with a roller spacing of 5mm and thin pass three times, a roller spacing of 2mm and thin pass five times, triangle wrapping three times, and sheeting to obtain a sheet; finally, the sheet is put into a mold for molding, the mold temperature is 195°C, the pressure is 8MPa, the molding is 5min, and the mold is cooled and demolded to obtain a temperature-controlled resin material.
7. Use of the temperature-control resin material according to any one of claims 1 to 5 on a shoe sole.
Citation Information
Patent Citations
Self-temperature adjustment insulation protective material and preparation method thereof
CN110423470A
Composite material for wear-resistant shoes and preparation method thereof
CN117362985A